Helping and harming - Patel, M (2019)
After Darwin (1858) presented the idea of evolution by natural selection scientists focused on the idea of fitness as the personal reproductive success of an individual. Hamilton (1964) gave birth to social evolution by defining what fitness means for a social trait, such as helping another individual by raising their young or harming them by stealing their food. In this thesis we look at the two most unintuitive forms of social behaviour: altruism and spite. In both an individual sacrifices its own personal fitness to help (altruism) or harm (spite) another individual. In my chapters I cover: (i) how the altruistic production of virulence factors in a pathogen can lead to strong frequency and density dependent effects when they are under a volunteer's dilemma, (ii) how these strong effects can lead to year-to-year fluctuations in bacterial virulence and the risk of epidemics, (iii) an argument against indiscriminate spite being possible in finite populations and argue that some previous examples are better classified as selfish indiscriminate harming, and (iv) how spiteful interactions between symbionts can lead to a host evolving higher relatedness amongst the symbionts and eventually result in close mutualisms between the symbiont and the host.